THE POLICY OF FINANCING THE STUDIES IN LITHUANIAN HIGHER EDUCATION: HISTORICAL DEVELOPMENT AND CONSEQUENCES OF INTRODUCING THE “STUDENT BASKET” - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2013)
The article deals with the policy of financing the studies in Lithuanian higher education during the last two decades. After regaining the independence in 1990, Lithuania inherited the Soviet model of financing of higher education where all higher educational institutions were state-owned and all studies were-state funded. However, quite soon the first full fee-paying students and the so-called “commercial groups” appeared in state higher education institutions as a result of the newly gained institutional autonomy. Eventually, non-state higher education institutions were established, and the number of full fee-paying students had been radically increasing until in 2000 the Law on Higher Education introduced a new model of funding – a fixed study fee of 1000 litas, which only partially covered the study costs. Thus, three categories of students emerged – state-funded, full fee-paying, and a fixed study fee paying students. In 2009, the Law on Studies and Research introduced a new model – the formula funding, which was popularly called “the student basket”. The entrants entitled to state funding after successfully passing the national matura exams were allowed to carry the state money “basket” to the university for the study program of their choice. The article notes that the intention of the reformers was to introduce market regulation instead of state regulation in this field in order to increase competition among higher education institutions and thus to ensure the quality of studies. Still another aim was to re-distribute students between the university and the non-university sectors in favour of the non-university sector. However, the aim was only partially achieved. The statistics presented in the article show that both in the university and the non-university sectors the entrants prefered to choose popular programs of universities in big cities, mainly in the fields of humanities and social sciences. As a result, regional universities and colleges as well as study programs related to science and technologies lost substantial numbers of students. These losses were partially compensated by enrolling larger numbers of full-fee-paying students.
Keywords: higher education policy; financing of studies; state regulation; market model; „student basket“